2022
DOI: 10.1186/s13012-022-01213-8
|View full text |Cite
|
Sign up to set email alerts
|

Systems analysis and improvement approach to optimize outpatient mental health treatment cascades in Mozambique (SAIA-MH): study protocol for a cluster randomized trial

Abstract: Background Significant investments are being made to close the mental health (MH) treatment gap, which often exceeds 90% in many low- and middle-income countries (LMICs). However, limited attention has been paid to patient quality of care in nascent and evolving LMIC MH systems. In system assessments across sub-Saharan Africa, MH loss-to-follow-up often exceeds 50% and sub-optimal medication adherence often exceeds 60%. This study aims to fill a gap of evidence-based implementation strategies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Our current work aims to facilitate future adaptations while maintaining reproducibility. Specific work exploring mechanisms of action (and the relative contributions of individual components of SAIA) is underway and will build upon the generalizability of the SAIA, including through the use of longitudinal structural equation modeling [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our current work aims to facilitate future adaptations while maintaining reproducibility. Specific work exploring mechanisms of action (and the relative contributions of individual components of SAIA) is underway and will build upon the generalizability of the SAIA, including through the use of longitudinal structural equation modeling [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our review also identified several protocols of trials that will assess the cost-effectiveness of different implementation strategies to scale-up task-shifting interventions for mental health disorders in sub-Saharan Africa. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…The SAIA-SCALE study, testing SAIA for PMTCT services in Mozambique, measured fidelity through a tablet-based survey completed by clinic staff to track number of SAIA cycles, attendants at each cycle meeting, and the number, content, and results of micro-interventions tested [ 33 ]. Two additional studies in Mozambique using SAIA for hypertension and mental health services assessed fidelity as number and frequency of SAIA cycles completed [ 10 ] and adherence to the 5-step SAIA cycle [ 34 ]. All three studies then categorized clinics as high or low performing and used focus group data to assess features of successful implementation.…”
Section: Discussionmentioning
confidence: 99%